Implementation of family life and HIV/AIDS education in Nigerian schools:a qualitative study on scope, delivery and challenges (2015)
This study utilized data from Focus Group Discussions and In-depth Interviews among secondary school students and teachers to examine the scope, delivery and challenges of FLHE implementation within states and across geopolitical zones in Nigeria. Structural Functionalism, Rational Choice and Differential Association theories were adopted as theoretical framework. Results show that several patterns in classroom teaching of FLHE are identifiable across the country. The study found that FLHE is taught at the Junior Secondary and Senior Secondary levels with variations among States on the beginning levels. The main mode of FLHE delivery is classroom instruction; other modes include assembly talk and sensitization by organizations. Despite paucity of Information, Education and Communication materials and inadequate personnel requirement, different stakeholders noted that FLHE has been beneficial to students. Therefore, effective implementation of FLHE will go a long way to ensuring that young people in Nigeria are equipped with necessary information to enable them exhibit the right attitude and behaviour towards sexuality issues.